2020
DOI: 10.1126/science.aax8201
|View full text |Cite
|
Sign up to set email alerts
|

Helical quantum Hall phase in graphene on SrTiO 3

Abstract: The ground state of charge neutral graphene under perpendicular magnetic field was predicted to be a quantum Hall topological insulator with a ferromagnetic order and spin-filtered, helical edge channels. In most experiments, however, an otherwise insulating state is observed and is accounted for by lattice-scale interactions that promote a broken-symmetry state with gapped bulk and edge excitations. We tuned the ground state of the graphene zeroth Landau level to the topological phase via a suitable screening… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 51 publications
5
84
0
2
Order By: Relevance
“…For a better comparison with the previously discovered helical QH phase in graphene 20 , 21 , we zoom in the R xx and R yx data in the Chern insulator regime, as displayed in Fig. 4a .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a better comparison with the previously discovered helical QH phase in graphene 20 , 21 , we zoom in the R xx and R yx data in the Chern insulator regime, as displayed in Fig. 4a .…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the QAH plateau will not survive forever because extreme conditions may induce other topological phases, as exemplified by the fractional QH effect 19 . Recently, it was demonstrated that helical phases analogous to the QSH phase exist in charge-neutral graphene 20 , 21 and non-symmorphic KHgSb crystal 22 in strong magnetic fields, which are characterized by quantized longitudinal resistance ( R xx ) and zero Hall resistance ( R yx ) plateau in certain magnetic fields and gate voltage ( V g ) ranges. Inspired by these discoveries, it is imperative to find out the fate of the Chern insulator phase in MnBi 2 Te 4 in strong magnetic fields, as has been discussed theoretically for magnetic TIs 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…4A and 4B of Ref. [7]) actually suggest that the most accurate quantization happens at T = 90K, rather than at T = 5K. That, along with the negative (albeit fairly small) temperature coefficient of the resistance dR/dT may warrant further studies.…”
mentioning
confidence: 90%
“…In the experiment [7], the graphene sheet was separated by mere 2 − 5nm of a HBN spacer from SrTiO 3 substrate. The latter has a huge ∼ 10 4 and may provide the dielectric screening for the electron-electron interaction in graphene.…”
mentioning
confidence: 99%
“…More importantly, the inability to stabilize patterned graphene edges [4][5][6] derailed the ambitious graphene nanoelectronics effort replacing it with much more modest goals. 16,17 Evidence of the protected graphene edge state [7][8][9][12][13][14] (not to be confused with quantum Hall edge states 14,[18][19][20][21][22][23][24] ) was first found in 40 nm wide self-assembled graphene ribbons that form 25 on the high temperature annealed sidewalls of steps etched on the polar faces of electronics grade hexagonal SiC. 26,27 Electron microscopy revealed that the sidewall ribbons terminated in the SiC, thereby stabilizing and passivating the edges.…”
mentioning
confidence: 99%